Immune-enhancing efficacy of Curtobacterium proimmune K3 lysates isolated from Panax ginseng beverages in cyclophosphamide-induced immunosuppressed mice. (May 2022) - Xu, Xing Yue; Dhandapani, Sanjeevram; Mi, Xiao Jie; Park, Hye-Ryung; Kim, Yeon-Ju
Graphical abstract: Highlights: Curtobacterium proimmune K3 lysates (Ly) was isolated from Panax ginseng beverages. Ly secreted greatly immune-related cytokines in mouse splenocytes. Ly increased production of cytokines in CTX-induced immunosuppressed mice. Ly phosphoraylated NF‐κB (p65-IκBα) and MAPK (JNK, ERK and p38) signaling pathways. Ly ameliorated the gut microbiota in the immunosuppressed mice. Abstract: In this study, the effects of Curtobacterium proimmune K3 lysates, isolated from Panax ginseng beverages, on splenocytes and cyclophosphamide (CTX)-induced immunosuppressed mice were investigated. Treatment with C. proimmune K3 lysates stimulated splenocyte proliferation and increased cytokine secretion in vitro and splenocytes ex vivo . Treatment with C. proimmune K3 lysates alleviated CTX-induced immunosuppression by modulating innate immunity in vivo, by recovering immune organ index and natural killer cell cytotoxicity, as well as by stimulating the adaptive immune system, via restoration of splenic lymphocyte proliferation, delayed-type hypersensitivity response, and IgG and IgA content. Moreover, C. proimmune K3 lysates treatment remarkably enhanced cytokine production in the spleen and thymus, compared with CTX-immunosuppressed mice. Our results suggest C. proimmune K3 lysates hold potential as a novel immunomodulatory agent for use in therapeutic purposes or as an ingredient in functional foods.